Behavior of laying hens in a cage free system at different ages and egg quality - Leite, Renata Gimenes (2021)
The production of eggs in Brazil has grown, which has led to an increase in the density of animals in the facilities, generating a decrease in ambience and well-being. Thus, this study aimed to carry out an analysis in laying systems, laying cage free without enrichment and cage free with enrichment, at the peak and end of production and its relationship with environmental enrichment and egg quality. For the treatment with enrichment were used: nest, perch, rattle, bales of native grass and branches of Cambuci. While the treatment without enrichment had only one nest, both treatments had feeders of the tubular type, drinkers of the pendular type and bed of rice straw. Animal behavior and egg quality were evaluated. In the behavior analysis, we obtained a difference between nesting, perching, scratching, chasing and scratching head behaviors, possibly due to the fact that birds use the means that were provided and can express their natural behavior. Within egg quality, we observed a difference in the parameters of yolk color, weight, albumen height, Haugh unit, shell thickness and yolk index (YCF), where yolk weight and color were higher in the treatment without enrichment, which may be due to the greater consumption of food, since the birds in this treatment did not have other means of distraction. It is concluded that enrichment promotes positive changes both in the expression of natural laying behaviors and improves the main requirements in relation to egg quality.